The allocation of competencies in an international union: a positive analysis - Michele Ruta (European Central Bank (ECB), 2003)
This paper presents a positive theory of centralization of political decisions in an international union. My central claim is that lobbies play a role in determining the assignment of competencies to the union because their power of influence can increase or decrease under centralization. I show that in this setting a misallocation of prerogatives between the international union and national governments can be an outcome, both leading to excessive decentralization and/or non necessary centralization. This result reconciles a partial inconsistency that recent studies pointed out between the allocation of prerogatives in the EU and normative criteria, as laid out in the theoretical literature.
Keywords: F02; D72; H77; P16; 330